Effect of grain sorghum particle size and digest “M” enzyme treatment on performance of growing steers - Kessen, T.J.; Simms, D.D.; Kuhl, Gerry L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 73-day growing study utilizing 203 crossbred steers (681 lb) and a digestion trial examined the effect o f sorghum grain particle size on rumen fermentation, ration digestibility, and performance of growing steers fed 37% grain and 63% ground alfalfa. Dry-rolled grain sorghum p article sizes in both trials were about 2000, 1500, and 1000 microns, for the coarse- (CR), medium- (MR), and fine-rolled (FR) treatments , respectively. Coarsely rolled corn (2000 microns) was included as a positive control. In the growing study, half of sorghum was treated at feeding time with an enzyme product, Digest “M”. The rations were 35 to 37% dry grain plus ground alfalfa hay and supplement. Total ration dry matter, neutral detergent fiber, and starch digestibilities increased linearly (P<.02) with decreasing sorghum grain particle size. Rumen pH, ammonia and total volatile fatty acid concentrations, and acetate-to-propionate ratio were unaffected by grain type or particle size. Dry matter intake was not influenced by grain types or particle size. Steers fed FR sorghum gained 9% faster (P<.03) during the first 28 days and tended to gain faster (5%, P<.14 ) over the entire trial than those fed CR sorghum , with gains on MR sorghum being intermediate. FR sorghum produced 6% more efficient gains (P<.07) than CR, and MR grain was intermediate. Digest “M” enzyme treatment of the sorghum grain had no influence. Feed con versions of CR, MR, and FR sorghum were 93, 94, and 99% of corn. This research indicates that grain sorghum in high roughage backgrounding programs should have a maximum average particle size of 1000 microns.
Keywords: Beef; Grain sorghum; Particle size; Processing; Digestibility; Enzyme; Growing cattle